Microstructure observation and flavor substances excavation of Yunyan 87 tobacco leaves with different oil contents - Hu, Xianfeng; Xu, Wei; Zhang, Yubo; Pan, Shouhui; Xie, Yanlan; Liao, Rui; Yang, Shenggang; Wu, Youxiang; Deng, Daomao (Frontiers in Plant Science, 2025)
IntroductionThe oil content of tobacco leaves is intimately associated with their aromatic characteristics. This study aims to explore the microstructure and distinctive flavor substances of Yunyan 87 high-oil-content tobacco leaves.MethodsThe microstructure and characteristic flavor substances of Yunyan 87 tobacco leaves with different oil contents were analyzed using scanning electron microscope (SEM) and comprehensive two-dimensional gas chromatography coupled with time-of-flight mass spectrometry (GC×GC-TOF MS).ResultsThe results indicate that the surface of high-oil tobacco leaves was characterized by a high density of glandular hairs, primarily composed of short-stalked glandular hairs featuring enlarged glandular heads. A total of 1551 flavor substances were detected in high-oil tobacco leaves, compared to 1500 metabolites were identified in low-oil tobacco leaves. Among these flavor substances, eight exhibited up-regulated, while three were down-regulated. Notably, the oil-related substances hexadecanoic acid methyl ester and the aroma-related substances nonanoic acid methyl ester and pseudoionone were found to be significantly more abundant in high-oil tobacco leaves compared to their low-oil counterparts. Consequently, hexadecanoic acid methyl ester may serve as a reliable indicator for evaluating the oil content in tobacco leaves, while nonanoic acid methyl ester and pseudoionone could play crucial roles as flavor substances influencing the aroma of tobacco leaves.DiscussionThese findings provide a theoretical foundation for future research on the regulatory mechanisms underlying the synthesis of aroma-producing flavor substances in tobacco leaves.